PENGEMBANGAN INDUSTRI HALAL TERHADAP PERTUMBUHAN EKONOMI LOKAL KABUPATEN NGAWI JAWA TIMUR - Hamdani, Hamdani (Fakultas Ekonomi Bisnis Islam, 2025)
The development of the halal industry in Indonesia has shown a significant increase, reaching a growth rate of 9.1% in recent years. This growth indicates a transformation toward sustainable economic development. The halal industry covers various sectors, including food and beverages, fashion, cosmetics, pharmaceuticals, and Islamic finance. With a Muslim population of more than 241 million people, Indonesia holds tremendous potential to become a global hub for the halal industry.This study aims to analyze the impact of halal industry development on local economic growth in Ngawi Regency, East Java, focusing on the contribution of micro, small, and medium enterprises (MSMEs) engaged in food, beverage, and fashion sectors. The research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation involving MSME actors and relevant government institutions.The findings indicate that the development of the halal industry in Ngawi Regency has a positive impact on local economic growth through job creation, enhanced product competitiveness, and expanded export opportunities. However, several challenges remain, including limited understanding of halal certification, insufficient supporting infrastructure, and restricted access to Islamic financial services for MSMEs. Therefore, stronger collaboration among the government, Islamic financial institutions, and educational sectors is required to build a sustainable halal industry ecosystem in Indonesia.